Land Tenure and Legal Pluralism in Africa and Asia: Gender, Reform, and Recognition - Sutikno, Aldilla Yulia Wielys (Indonesian Scientific Publication, 2024)
This narrative review examines the interplay between customary land rights and statutory legal frameworks within plural legal systems, with a focus on land tenure security in sub-Saharan Africa and Southeast Asia. The objective is to assess how pluralism in land law affects the recognition and protection of customary land rights, particularly among marginalized communities. A systematic literature search was conducted using databases such as Scopus, Google Scholar, and PubMed. Keywords including